Dishonesty in the classroom and its link to the pursuit of academic excellence - Woodbine, Gordon; Amirthalingam, Vimala (General Commercial Publisher: International Journal of Arts & Sciences, 2012)
A controlled experiment was conducted with a cohort of graduate accounting students, which involved a mild form of deception during a class ethics quiz. One of the answers to a difficult question was inadvertently revealed by a visiting scholar, which allowed students an opportunity to use the answer in order to maximise test scores and qualify for a reward. Despite an attempt to sensitize students prior to the test to the importance of moral codes of conduct, a high incidence of cheating was reported. Students who took the opportunity to cheat were more condoning of the behaviour compared to control group members and students who did not use the disclosed answer and this difference in attitudes was consistent regardless of the intensity of the issue specified in the survey. A logistic regression indicated that cheating was more likely to occur amongst students who appeared to excel, although this was offset to some extent by their level of religious commitment. The cognitive dissonance associated with the academic dishonesty is believed to reveal behavioural orientations that reflect conscious and unconscious concerns about not achieving satisfactory standards of performance. These perceived fears and apprehensions result in inappropriate behaviours and appear to be unaffected by standard forms of ethics intervention.